Online Games as A Medium To Increase English Vocabulary For Elementary School Students - Khasanah, Shokhikhatul (Indonesian Journal Publisher, 2025)
Learning English early on can also help children acquire better language skills in general, including the ability to understand grammar and correct sentence structure. In the era of Industry 4.0 or the fourth industrial revolution is a term that is often used today which describes the level of development of the technology industry in the world. Games are one of the media for children to learn that can develop connitivous, social, emotional and physical students. In learning, a game needs to be made challenging and can motivate students. The research was conducted through a survey using a descriptive qualitative method where the researcher provided a survey questionnaire through a google form. Data analysis techniques carried out based on the results of observations, interviews, questionnaires The influence of online games in the acquisition of English vocabulary can certainly be used as one of the media in learning English. Playing online games is not only an entertainment and a place to have fun, but it can also be used as a means of learning English.